The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/jabs-03-2018-0083
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership style, followership, and factors of employees’ reactions towards organizational change

Abstract: Purpose This study aims to investigate the relationship between transformational leadership style and factors of employees’ reactions towards organizational change in the telecommunication sector of Pakistan. Furthermore, to understand the importance of followership it has been analyzed as a moderating variable in the relationship between transformational leadership style and factors of employees’ reactions. Design/methodology/approach A mixed methods study design was applied to investigate the factors under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 123 publications
1
59
0
1
Order By: Relevance
“…The best way is to focus on human resources as the capital asset for successful organizational change. As stated by Busari et al (2019), the successful implementation of change in organizations is determined by employees as followers and leaders with transformational leadership behavior. They play an important role in shaping positive reactions to changes in the organization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The best way is to focus on human resources as the capital asset for successful organizational change. As stated by Busari et al (2019), the successful implementation of change in organizations is determined by employees as followers and leaders with transformational leadership behavior. They play an important role in shaping positive reactions to changes in the organization.…”
Section: Discussionmentioning
confidence: 99%
“…Transformational leadership received great attention from researchers since it was found to greatly influence leadership practices. There is increasing evidence by the scholars on the role of transformational leadership as an appropriate approach in enhancing organizational change (e.g Van der Voet et al, 2016;Middleton et al 2015;Mwangi and Kwasira, 2015;Chou, 2014;Busari et al, 2019;Carter et al, 2013;Feng et al, 2016;Howarth and Rafferty, 2009;Holten and Brenner, 2015). According to Yulk (2010), transformational leadership is a specific leadership approach that focuses on the abilities of a leader as a process to change and transform employees through increasing motivation to work, establishing high commitment, and empowering employees in efforts to achieve organizational goals.…”
Section: Introductionmentioning
confidence: 99%
“…Transformational leadership is an effective leadership style in most organizations because the leaders who follow this model understand how to inspire followers to go beyond the norm (Apore and Asamoah, 2019). Many researchers have suggested that transformational leadership is the ideal leadership style for dealing with organizational change because the leaders who utilize it understand how to develop others to assume tasks (Busari et al, 2019). Additionally, research has shown that transformational leadership is highly desirable for influencing organizational change in the healthcare industry (Al-Hussami et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…According to Kirkan (2011), transformational leadership is a leadership pattern used by leaders to change the current situation by following those who follow the organizational problem through inspiration, persuasion, and excitement to achieve a higher understanding of the vision for the realization of shared goals within the organization. Besides that, transformational leaders act as agents of change by stimulating and changing motivation, attitude, and increasing the trust of their members (Busari et al,2019).…”
Section: Transformational Leadership Stylementioning
confidence: 99%